Combating Rheumatoid Arthritis with Berberine and Curcumin: A Review of Natural Therapeutics - Naik, B Babji; Priya, A Vamsi; G Sowjanya, G Sowjanya; Sekhar, K Indra; Naik, N Sojen; Abdelrahman, Fadul; Bhargav E, Bhargav E (Journal of Neonatal Surgery, 2025)
Rheumatoid arthritis (RA) is a long-term inflammatory disease that causes synovial joint inflammation, which causes pain, stiffness, and gradual joint destruction. In addition to having a major effect on quality of life, the illness may result in systemic problems. The goal of current treatment approaches, which include biologics, corticosteroids, disease-modifying antirheumatic medications (DMARDs), and nonsteroidal anti-inflammatory medicines (NSAIDs), is to manage symptoms and halt the course of the disease. These treatments, however, frequently have problems like poor effectiveness, systemic side effects, and exorbitant expenses. Advanced, tailored medication delivery methods like nanocarriers are necessary because managing RA is made more difficult by poor patient adherence and limited targeting of inflammatory areas. Berberine and curcumin are bioactive natural compounds with significant therapeutic potential, particularly in managing inflammatory and autoimmune conditions like rheumatoid arthritis (RA). Berberine exhibits potent anti-inflammatory, immunomodulatory, and antioxidant properties, effectively suppressing pro-inflammatory cytokines and oxidative stress Curcumin, a polyphenol derived from turmeric, also demonstrates strong anti-inflammatory and antioxidant effects, inhibiting key molecular pathways involved in RA pathogenesis, such as NF-κB activation. Despite their promising pharmacological profiles, both compounds face challenges like poor water solubility, low bioavailability, and rapid metabolism. Advanced drug delivery systems, such as nanostructured lipid carriers, offer a solution to enhance their therapeutic efficacy and clinical applicability. Nanostructured lipid carriers (NLCs) are advanced drug delivery systems offering numerous advantages for therapeutic applications. Their unique structure, combining solid and liquid lipids, enhances drug solubility, stability, and bioavailability. NLCs enable controlled and sustained drug release, reducing dosing frequency and improving patient compliance. They can protect sensitive drugs like berberine and curcumin from degradation, extending their shelf life. Additionally, NLCs can be functionalized for targeted delivery, increasing drug accumulation at inflamed joints in conditions like rheumatoid arthritis while minimizing systemic side effects. Their biocompatibility and scalability make NLCs a promising platform for improving the clinical efficacy of challenging therapeutic agents. Berberine and curcumin exhibit remarkable anti-inflammatory and antioxidant properties, making them promising candidates for managing rheumatoid arthritis (RA). However, their clinical potential is limited by poor solubility and bioavailability. Nanostructured lipid carriers (NLCs) address these limitations by enhancing drug stability, targeted delivery, and controlled release. Preclinical studies demonstrate improved therapeutic efficacy of NLC formulations in RA models, though clinical translation remains limited. Future research should focus on optimizing NLC designs for enhanced targeting, scalability, and regulatory compliance. Combining these carriers with advanced therapeutic strategies offers a pathway to more effective and patient-friendly RA treatments, bridging lab discoveries to clinical practice